Targeting alveolar macrophages shows better treatment response than deletion of interstitial macrophages in EGFR mutant lung adenocarcinoma. Issue 2 (3rd March 2020) - Alikhanyan, Kristina; Chen, Yuanyuan; Kraut, Simone; Sotillo, Rocio
Abstract: Introduction: Alveolar macrophages (AMs) are critical in the development of lung adenocarcinoma driven by epidermal growth factor receptor (EGFR) mutations. Whether interstitial macrophages (IMs) are also involved in lung tumorigenesis is still unclear. Thus, the aim of this study is to evaluate the role of both AM and IM in the development of EGFR mutant driven lung adenocarcinoma. Methods: We used the EGFR mutant doxycycline‐inducible mouse model of lung adenocarcinoma to deplete interstitial or AMs by clodronate‐encapsulated liposomes administered intravenously (IV) and intratracheally (IT), respectively. Tumor burden, AMs, and the tumor microenvironment were examined by immunohistochemistry, bronchoalveolar lavage fluid or flow cytometry. Results: Clodronate treatment resulted in a significant reduction of tumor burden compared with vehicle liposomes alone. Elimination of AMs resulted in a significant reduction of proliferation compared with IV treatment. However, both treatments resulted in a significantly higher number of Ki67 positive cells compared with control mice, suggesting that tumor cells still proliferate despite the treatment. The number of natural killer cells decreased during tumor development, and it remained low even after the elimination of AMs. We also observed that IT instillation of clodronate significantly increased the number of CD8+ T cells, which was higher compared with vehicle‐treated mice and mice where only IMs were depleted. The similar trend was observed in immunohistological analyses of CD8+ T cells. Conclusions: These results suggest that the reduction of AMs has a stronger impact on restricting tumor progression compared with targeting IMs. The depletion of AMs leads to an elevated infiltration of CD8+ T cells into the lung that might be responsible for tumor growth impairment. Altogether, elimination of AMs is a better strategy to reduce EGFR mutant tumor growth and is less toxic, suggesting the selectively targeting of AMs to complement established therapies. Abstract : We use a well‐characterized mouse model of epidermal growth factor receptor (EGFR) mutant lung adenocarcinoma and show that depletion of alveolar macrophages (AMs) has a strong impact on restricting lung tumor progression. We further show that the ablation of interstitial macrophages has a milder effect on tumor growth. In addition, we show that depletion of AMs leads to an increased infiltration of CD8+ T lymphocytes that might be responsible for the reduction of tumor growth.